2021
DOI: 10.1186/s13012-021-01178-0
|View full text |Cite
|
Sign up to set email alerts
|

Implementation strategies and outcomes for occupational therapy in adult stroke rehabilitation: a scoping review

Abstract: Background Stroke survivors often encounter occupational therapy practitioners in rehabilitation practice settings. Occupational therapy researchers have recently begun to examine the implementation strategies that promote the use of evidence-based occupational therapy practices in stroke rehabilitation; however, the heterogeneity in how occupational therapy research is reported has led to confusion about the types of implementation strategies used in occupational therapy and their association … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 85 publications
0
20
0
Order By: Relevance
“…To synthesize data, we used the progression bounding method recommended by Levac et al, 38 Since scoping reviews do not summarize or measure evidence from studies, 38,39 in our study only descriptive analyses (such as frequency and percentage) were performed on the extracted data to describe the findings of the included studies. 40 The descriptive data and findings of all included articles were organized in the format of tables and figures based on themes to present the findings of the present study, which guided the objectives of the study. In case of disagreement by any of the authors, the final decision about each figure or table was reached through discussion.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To synthesize data, we used the progression bounding method recommended by Levac et al, 38 Since scoping reviews do not summarize or measure evidence from studies, 38,39 in our study only descriptive analyses (such as frequency and percentage) were performed on the extracted data to describe the findings of the included studies. 40 The descriptive data and findings of all included articles were organized in the format of tables and figures based on themes to present the findings of the present study, which guided the objectives of the study. In case of disagreement by any of the authors, the final decision about each figure or table was reached through discussion.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Our review found games can cause “Improvement in musculoskeletal performance,” “Increasing users' enjoyment/joy of therapeutic exercises and their motivation to perform these exercises,” “Therapy compliance and acceptability by patients,” and “Increasing adherence to treatment and performing rehabilitation exercises.” Some review studies 4,40 also showed that virtual reality and rehabilitation games can increase the patient's motivation to perform exercises, improve upper limb function, improve independence in day‐to‐day activities, and improve upper limb range of motion, as well as strengthen neural connections and cause reorganization in different areas of the cerebral cortex related to the injured limb, leading to improved motor performance 59 . Virtual reality‐based games boost motor learning.…”
Section: Discussionmentioning
confidence: 99%
“…The results they obtained allowed them to highlight the most effective methods and procedures. In particular, based on the experience of comprehensive rehabilitation of the masticatory-speech apparatus impaired in patients as a result of stroke and craniocerebral trauma, neurologists gave preference to the method of restorative training of patients [29][30][31].…”
Section: Basic Geriatric Syndromes and Diseases-their Importance In T...mentioning
confidence: 99%
“…Common strategies include training, educating, audit, and feedback, including engagement with stakeholders (clinicians, executive boards, community services, academic partnerships, and policy makers). A discrete group of strategies have been identified through codesign and scoping reviews to promote practice guideline implementation in hospital settings, and form the basis for understanding the mechanisms of change when developing implementation trials . For sustained use and lasting change, a recent review of research in hospital-based smoking cessation interventions emphasizes the use of multiple strategies.…”
Section: Introductionmentioning
confidence: 99%